2018
DOI: 10.4314/gjedr.v13i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Human resources management and lecturer’s job satisfaction in tetiary institutions in Akwa Ibom and Cross River States

Abstract: The study examines the extent to which the management of human resources by the administrators influence lecturers' job satisfaction in tertiary institutions in Akwa Ibom and Cross River States, Nigeria. The ex-post-facto research design was used for the study. The population of the study was 2286 lecturers from nine (9) tertiary institutions from the two states out of which 600 lecturers were randomly sampled from six (6) tertiary institutions in the two states. The statistical analysis used to test the only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Etor [14] concluded that school administrators should create an enabling environment for lecturers to work and alleviate work that are too strenuous, this will help to eliminate frustration and feeling of failure. It is believed that situation of minimal task, most employees will have the sense of fulfilment and job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Etor [14] concluded that school administrators should create an enabling environment for lecturers to work and alleviate work that are too strenuous, this will help to eliminate frustration and feeling of failure. It is believed that situation of minimal task, most employees will have the sense of fulfilment and job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, without staff, post-graduate programmes will not only be non-effective but there will also be no post-graduate programmes at all. Although the mere presence of staff is not enough to make post-graduate programmes effective, they must be properly placed, assigned tasks, guided accordingly, given the appropriate working conditions, motivated, supervised strictly and evaluated consistently to ensure they work in line with goals and objectives of the programmes [21][22]. All these series of activities are what constitute staff management, and proper/consistent delivery of such administrative duties will promote the effective prospect of post-graduate programmes in Cross River State and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting connection between human relationships (interpersonal partnerships, teacher involvement, and mandate delegation) and teacher work in secondary schools was revealed in recent research (Arop et al, 2019). Other research has also shown a significant relationship between human capital management and employee happiness in higher education (Etor, 2014). However, none of the cited studies assessed the management of human resources in connection with the fulfilment of school goals at the secondary education level.…”
Section: Studies On Non-financial Resourcesmentioning
confidence: 98%